Kesalahan Berbahasa Tataran Sintaksis pada Teks Eksposisi Siswa Kelas X-3 SMAN 3 Jember - Dina Rimadani (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research examines language errors at the syntactic level found in exposition texts by class X-3 students at SMAN 3 Jember. This research was carried out because based on the results of observations, syntactic language errors were found in class X-3. These errors are caused because many students do not know good writing skills according to the syntactic level. The aim of this research is to identify forms of syntactic errors that occur in student assignments. This research uses qualitative research because it uses descriptive data in the form of written language errors from the students being observed. This research uses the documentation method. The data in this study are sentences that are suspected to contain language errors at the syntactic level. The data source in this research is the exposition text of class X-3 students at SMAN 3 Jember. The results of this research show forms of language errors at the syntactic level in the field of phrases, namely errors found due to inappropriate use of prepositions. Apart from that, in the field of sentences, pay attention to syntactic errors related to sentence structure. Some of the errors found from research on syntactic level language errors found in exposition texts written by class ) Sentences that are inserted between the predicate and the object, (4) Sentences that Use Excessive Conjunctions, (5) Sentences whose Sequence is Not Parallel, (6) Sentences that Use Unnecessary Question Words. It is hoped that the results of the analysis and findings from this research can provide insight for teachers in designing more effective learning strategies in improving students' syntactic abilities in writing expository texts.
Reaploud Repository February_Hasyim
Keywords: Syntax errors; Exposition text; Syntax